Pattern of Live Births in Rio de Janeiro State, Brazil, According to Robson Groups and the Kotelchuck Index Classification - 2015/2016 - Luciana Leite de Mattos Alcantara; Núbia Karla de Oliveira Almeida; Renan Moritz Varnier Rodrigues de Almeida
Abstract Objective To investigate the patterns of hospital births in the state of Rio de Janeiro (RJ), Brazil, between 2015 and 2016; considering the classification of obstetric characteristics proposed by Robson and the prenatal care index proposed by Kotelchuck. Methods Data obtained from the Information System on Live Births of the Informatics Department of the Brazilian Unified Health System (SINASC/DATASUS, in the Portuguese acronym) databases were used to group pregnant women relatively to the Robson classification. A descriptive analysis was performed for each Robson group, considering the variables: maternal age, marital status, schooling, parity, Kotelchuck prenatal adequacy index and gestational age. A logistic model estimated odds ratios (ORs) for cesarean sections (C-sections), considering the aforementioned variables. Results Out of the 456,089 live births in Rio de Janeiro state between 2015 and 2016, 391,961 records were retained, 60.3% of which were C-sections. Most pregnant women (58.6%) were classified in groups 5, 2 or 3. The percentage of C-sections in the Robson groups 1, 2, 3, 4, 5 and 8 was much higher than expected. Prenatal care proved to be inadequate for women who subsequently had a vaginal delivery, had an unfavorable family structure and a lower socioeconomic status (mothers without partners and with lower schooling), compared with those undergoing cesarean delivery. For a sameRobson group, the chance of C-section increases when maternal age rises (OR = 3.33 for 41-45 years old), there is the presence of a partner (OR = 1.81) and prenatal care improves (OR = 3.19 for "adequate plus"). Conclusion There are indications that in the state of RJ, from 2015 to 2016, many cesarean deliveries were performed due to nonclinical factors.